Crystal structure, infrared spectroscopy and microwave dielectric properties of ultra low-loss Li2Mg3Ti0.95(Mg1/3Sb2/3)0.05O6 ceramic. Issue 3 (15th February 2018) - Pan, H.L.; Zhang, Y.W.; Wu, H.T.
Abstract: Ultra low-loss Li2 Mg3 Ti0.95 (Mg1/3 Sb2/3 )0.05 O6 ceramic with a cubic rock-salt structure was prepared by the conventional solid-state reaction method. The crystal structure, sintering characteristics, microwave dielectric properties, intrinsic parameters and infrared spectrum were investigated systematically. Refined crystal structure was obtained using the Rietveld refinement method. Based on the chemical bond theory, some intrinsic parameters were calculated and Ti–O bonds played an important role in influencing microwave dielectric proprieties. According to the infrared analysis, the major polarization contribution attributed to the absorption of phonon oscillations. A few of (Mg1/3 Sb2/3 ) 4+ -substitutions obviously improved the microwave dielectric properties of Li2 Mg3 TiO6 ceramic. Excellent microwave dielectric properties of ε r = 14.40, Q·f = 195, 500 GHz and τ f = −4.02 ppm/°C were obtained for Li2 Mg3 Ti0.95 (Mg1/3 Sb2/3 )0.05 O6 ceramic sintered at 1575 °C.